Edukasi Titik Kritis Kehalalan Produk Pangan, Kosmetik, dan Obat-Obatan Menggunakan Flowchart pada Siswa Sekolah Menengah Analis Kimia (SMAKPA) Padang - Dini Hanifa; Rustini Rustini; Purnawan Pontana Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Halal products are crucial for consumers. In Islam, halal and wholesome food consumption is vital for maintaining physical and spiritual well-being. The Indonesian government mandates halal product certification by Law No. 33 of 2014 on Halal Product Assurance. The critical points in determining the halal status of a product refer to processes or ingredients in its production that may potentially involve, contain, or mix with haram substances. Nevertheless, many students lack a clear understanding of halal and haram principles. This knowledge is essential to help students avoid using forbidden ingredients in Islamic teachings. Padang Chemical Analyst High School (SMAKPA) students are the targets of this service because vocational school students must have work-ready skills. Before the education session, a pre-test was conducted to assess the student's understanding of the material presentation. Education was delivered using a flowchart to enhance engagement and comprehension. The content encompasses the concepts of halal and haram in Islam, the responsible parties for halal certification, halal logos, and the analysis of critical points in the halal status of food, cosmetics, and medications. Following the material presentation, a post-test was administered, followed by a question and answer session to evaluate the students' understanding. Pre-tests and post-tests were employed to assess student comprehension, with pre-test scores averaging 99 and post-test scores at 99.5. Through this educational initiative, students gain a comprehensive understanding of the Critical Points of Halal Status in Food, Cosmetics, and Medications using a flowchart